2005
DOI: 10.1021/jf050582+
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Scavenging Effect of Enzymatic Extracts from Sargassum thunbergii

Abstract: The free radical scavenging activity of water soluble natural antioxidants from Sargassum thunbergii, which is a brown marine alga, was evaluated by examining the radical scavenging activities of the extracts of hydrolyzates from S. thunbergii on hydroxyl, 1,1-diphenyl-2-picrylhydrazyl (DPPH), and alkyl radicals. A spin-trapping electron spin resonance (ESR) spectrometer was employed, and the results were compared for their ESR signal intensity. S. thunbergii was enzymatically hydrolyzed to prepare water solub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(62 citation statements)
references
References 27 publications
0
62
0
Order By: Relevance
“…The Korean ginseng leaf powder (3 g) was rehydrated with distilled water (DW, 50 mL) and 0.5 wt% Ultraflo L was added at 40°C for 12 hours to hydrolyze cellulose and pectin in the ginseng leaf [16][17][18]. The hydrolyzed mixture was extracted twice with 150 mL of ethanol under reflux in a water bath at 90°C for 2 hours.…”
Section: Preparation Of Korean Ginseng Leaf Extractionmentioning
confidence: 99%
“…The Korean ginseng leaf powder (3 g) was rehydrated with distilled water (DW, 50 mL) and 0.5 wt% Ultraflo L was added at 40°C for 12 hours to hydrolyze cellulose and pectin in the ginseng leaf [16][17][18]. The hydrolyzed mixture was extracted twice with 150 mL of ethanol under reflux in a water bath at 90°C for 2 hours.…”
Section: Preparation Of Korean Ginseng Leaf Extractionmentioning
confidence: 99%
“…Attention of researchers was focused on the ability of algae to accumulate antioxidant compounds. Heo et al (2005) identified the potential antioxidant compounds as some pigments (e.g. chlorophyll, carotenoid) and polyphenols (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, they are used in medicine and in pharmacology for their antimicrobial, antiviral, antitumor and anticoagulant properties (Fleurence, 1999 andSabina et al, 2005). Recent studies show the antioxidant abilities of many types of seaweeds (Lim et al, 2002;Park et al, 2005;Duan et al, 2006 andKuda andIkemori, 2009). Marine algae, like other photosynthesizing plants, are exposed to different environmental conditions that lead to the generation of reactive oxygen species (Asada, 1999).…”
mentioning
confidence: 99%
“…11) In this context, the lily pollen-based system might be proposed as a potential edible vaccine vector for direct and rapid application.…”
Section: Notementioning
confidence: 99%